Consumer Perceptions and Preferences for Mobile Payment Systems - Bhandari , Yubraj (KIC International Journal of Social Science and Management, 2024)
This study aims to examine consumer perceptions and preferences for mobile payment systems in the Nepali market. As there is an increasing trend in the usage of digital and mobile banking payment systems in Nepal, it is crucial to understand consumer perceptions towards mobile banking systems so as to investigate how these perceptions influence the consumers' preference to adopt mobile payment systems in their transactions. Thus, this study analyses the influence of perceived usefulness, ease of use, security, and trust (independent variables) on consumers’ preferences (dependent variable) of mobile payment systems. The data for this study was collected from 251 mobile banking users selected conveniently and obtained their responses on the dependent and independent variables. The data analyzed by the means of correlation and regression tool of analysis indicates that perceived usefulness, ease of use, security, and trust significantly influence consumer preference for mobile payment systems. Thus, the results of this study could provide valuable insights to financial institutions and mobile payment service providers to enhance the quality of the services and develop strategies to cater to their consumer needs more effectively.